Assessing the compressive elasticity and multi-responsive property of gelatin-containing weakly anionic copolymer gels via semi-IPN strategy. Issue 37 (13th September 2022) - Ciftbudak, Sena; Orakdogen, Nermin
Abstract : A simple and efficient approach for the design of gelatin-containing weakly anionic semi-IPNs has been proposed. Abstract : A series of semi-interpenetrating polymer network (semi-IPN) hydrogels based on acrylamide (AAm) and itaconic acid (ITA) was prepared in the presence of different amounts of the natural polymer gelatin (GLN). The semi-IPNs were synthesized by simultaneous polymerization using N, N ′-methylene bisacrylamide as a crosslinking agent. A pH-sensitive system was obtained by adding 2 mol% ITA as an anionic comonomer. The effect of GLN content by changing the amine/carboxyl functional groups and incorporating carboxyl groups of ITA in semi-IPN on the swelling, elasticity and physical properties of the hydrogels was investigated. The presence of GLN improved the thermal stability, and the GLN-containing semi-IPNs exhibited a higher degradation temperature compared to the GLN-free copolymers. The addition of a small amount of GLN could effectively increase the swelling of the semi-IPNs in water. By employing the GLN-containing semi-IPN as a model system, the solvent/matrix interactions were demonstrated to reveal the effect of solvent structure on the swelling-shrinkage response. The addition of GLN improved the pH-sensitivity of the semi-IPN gels, resulting in a clear response to pH change by action of NH3 + and COOH of GLN and additional COOH groups from ITA. The mechanical performance of the copolymer network was improved by entangling PAAm/ITA chains with GLN, which acted as a reinforcement node. In terms of the effect of Hofmeister anions on the swelling behavior, the anion effect became more pronounced with salt concentration. The affinity of semi-IPNs towards the cationic dyes methylene blue and malachite green was tested and the dependence of the adsorption process on the initial dye concentration, contact time and GLN content was determined. This method presents a simple and efficient approach for the design of chemically crosslinked protein-based gels for drug delivery applications.